Banking Risk Management ("Journal "U". Economy. Management. Finance.", 2021)
This article disclosed the essence of banking risk management, as well as methods and tools for assessing banking risks. The assessments of the degree of risk were characterized, the basic principles of building an intrabank risk management system were formulated and recommendations were given for building an effective system of banking risk management.
Keywords: banks; risks; banking risks; banking risk assessment; assessment methods; banking risk management system